2020
DOI: 10.1002/advs.202002419
|View full text |Cite
|
Sign up to set email alerts
|

FullyPrinted Flexible Plasmonic Metafilms with Directional Color Dynamics

Abstract: Plasmonic metafilms have been widely utilized to generate vivid colors, but making them both active and flexible simultaneously remains a great challenge. Here flexible active plasmonic metafilms constructed by printing electrochromic nanoparticles onto ultrathin metal films (<15 nm) are presented, offering low‐power electricallydriven color switching. In conjunction with commercially available printing techniques, such flexible devices can be patterned using lithography‐free approaches, opening up potential f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(40 citation statements)
references
References 57 publications
(81 reference statements)
0
35
0
Order By: Relevance
“…Devices made on Au‐coated poly(ethylene terephthalate) substrates showed high quality and durability with no observable damage upon bending (Figure S25, Supporting Information), meeting the requirements of large‐area flexibility for wearable and biomedical electronics. [ 10 ] The fact that the oxidant can also be deposited by printing techniques, such as screen printing, [ 21 ] shows further promise of the UV patterning approach for scalable production of fully printed devices.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Devices made on Au‐coated poly(ethylene terephthalate) substrates showed high quality and durability with no observable damage upon bending (Figure S25, Supporting Information), meeting the requirements of large‐area flexibility for wearable and biomedical electronics. [ 10 ] The fact that the oxidant can also be deposited by printing techniques, such as screen printing, [ 21 ] shows further promise of the UV patterning approach for scalable production of fully printed devices.…”
Section: Resultsmentioning
confidence: 99%
“…[ 2,8 ] Recent efforts to facilitate tuning or on/off switching of structural colors have combined optical nanocavities with conducting polymers, whose optical transparency can be controlled electrochemically. [ 1,9,10 ] The same redox dependence has made conducting polymers popular for electrochromic displays also without cavities, but typically limited to monochromic function. [ 11–13 ] As example, the popular conducting polymer PEDOT (poly[3,4‐ethylenedioxythiophene]) switches only between different shades of blue, while practical applications would preferably also cover other parts of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Soft plasmonics may have promising applications in wearable biosensors, the Internet of Things, artificial intelligence, and argumentation reality or virtual reality. To date, soft plasmonic materials and devices have exhibited interesting mechanical properties [ 13 ] and novel mechanoplasmonic properties controlled by force, [ 7–12,14–17 ] heat, [ 18–21 ] electrical potential, [ 22,23 ] light, [ 24–27 ] and chemicals. [ 28–30 ] A few earlier review/perspective articles reported until around 2015 described flexible terahertz and optical metasurfaces and metamaterials, as well as flexible nanoplasmonic sensing.…”
Section: Introductionmentioning
confidence: 99%
“…First, a discussion of various bottom‐up and top‐down fabrication methods for soft plasmonic structures and structural/mechanical/optical characterization is included ( Figure ). This is followed by the description of novel soft plasmonic material properties and applications in biological engineering, [ 34 ] flexible sensors, [ 20,35 ] flexible energy [ 36–38 ] /photonic [ 23,39 ] /electric [ 24 ] devices, and soft robotics. [ 40,41 ]…”
Section: Introductionmentioning
confidence: 99%
“…This results in an MIM geometry with gap size set by the thickness of the molecular layer ( d < 2 nm), identical across large areas (>100 cm 2 ). 32 However, access to these hotspots is confounded by the thick nontransparent Au mirror, restricting its utilization.…”
mentioning
confidence: 99%